Frequency and prescription patterns of laboratory investigations in evaluating physical morbidity among psychiatric inpatients – A cross-sectional study - Gargi Pushpalal; Sivaprakash Balasundaram; Karthick Subramanian; Mohamed Hanifah (Journal of Current Research in Scientific Medicine)
Background: Comorbid physical illnesses worsen the morbidity and mortality in patients with mental illness. There is inadequate consensus regarding the optimal level of laboratory investigations and there is a need to know regarding the assessment of physical morbidity. Our study was conducted to study the frequency of prescription of laboratory investigation in evaluating psychiatric inpatients in a tertiary care center. Materials and Methods: An observational cross-sectional study was conducted in the inpatient psychiatry unit of a tertiary care hospital for one and a half years. Patients diagnosed with any mental illness and required hospitalization were included in the study. Sociodemographic data, illness details, and data regarding frequency and indications of laboratory investigations were recorded using a semistructured pro forma. For inferential analysis, P ≤ 0.05 was considered statistically significant. Results: One hundred and sixty-two participants were included in the study. “Endocrine, nutritional, or metabolic diseases” were the most common preexisting and newly diagnosed group of physical illness. A total of 705 additional tests were ordered for the study sample. Blood biochemistry was the most frequently ordered investigation. The most frequent blood biochemistry test, hematological test, and imaging were the estimation of glycemic indices, complete blood count, and ultrasound abdomen, respectively. One in two additional laboratory tests had abnormal or out-of-reference range (ORR) values in the results. Hematological tests were the most common, with abnormal or ORR values, followed by imaging and blood biochemistry. Clinician judgment was the most frequent reason for ordering an additional investigation. Conclusion: The study revealed that age, gender, the type of psychiatric illness, and the illness course-related characteristics significantly influenced the prescribing frequency of additional investigations and the proportion of abnormal/outside reference range results.